Profound hearing loss following surgery in pediatric patients with posterior fossa low-grade glioma. Issue 2 (18th December 2017) - Ghazwani, Yahya; Qaddoumi, Ibrahim; Bass, Johnnie K; Wu, Shengjie; Chiang, Jason; Boop, Frederick; Gajjar, Amar; Sadighi, Zsila
Abstract: Background: Hearing loss may occur in patients with posterior fossa low-grade glioma who undergo surgery. Methods: We retrospectively reviewed 217 patients with posterior fossa low-grade glioma, including 115 for whom results of hearing tests performed after surgery and before chemotherapy or radiation therapy were available. We explored the association of UHL with age at diagnosis, sex, race, tumor location, extent of resection, posterior fossa syndrome, ventriculoperitoneal shunt placement, and histology. Results: Of the 115 patients, 15 (13.0%: 11 male, 6 black, 8 white, 1 multiracial; median age 7 years [range, 1.3–17.2 years]) had profound UHL after surgery alone or before receiving ototoxic therapy. Median age at tumor diagnosis was 6.8 years (range, 0.7–14.1 years), and median age at surgery was 6.8 years (range, 0.7–14.1 years). Patients with UHL had pathology characteristic of pilocytic astrocytoma (n = 10), ganglioglioma (n = 4), or low-grade astrocytoma (n = 1). Of these 15 patients, 4 underwent biopsy, 1 underwent gross total resection, 1 underwent near-total resection, and 9 underwent subtotal resection. UHL was more frequent in black patients than in white patients (OR 7.3, P = .007) and less frequent in patients who underwent gross total resection or near-total resection than in those who underwent subtotal resection (OR 0.11, P = .02). Conclusions: Children undergoing surgery for posterior fossa low-grade glioma are at risk for UHL, which may be related to race or extent of resection. These patients should receive postoperative audiologic testing, as earlier intervention may improve outcomes.